Dental Caries and the Early Diagnosis using Low Level Laser - Mahdi Ali Sukkar Al-Farawn (Journal of Global Pharma Technology, 2018)
The current comparative investigational work was performed to identify the reliability of the occlusal-caries-based (OC) detection using the laser fluorescence device (DD) and the traditional methods of visual-based inspection, probing-dependent detection, and periapical dental radiographs. Moreover, fissure sealant (FS) and fluoride-based topical application (FTA) was evaluated using the DD technique. Here, 60 patient molar teeth were selected for the current work from a school primary oral care center, Al-Najaf City during the years of 2016-2017. Those teeth were randomly divided based on the diagnostic tool used into VI, probing, dental x-ray, and DD (VPXD group, 40 teeth (females (n)= males (n) 6-7 years old) diagnosed as a positive sing or a negative sing for intact caries or an intact tooth respectively), FS application followed up with DD (FSD group, 10 teeth diagnosed before and after the application), and FTA followed up with DD (FTAD group, 10 teeth diagnosed before and after the application). The teeth were polished and then assigned to their diagnostic methods. The current work results identified that the DD was more reliable in detecting caries and evaluating FS and FTA than those in dental probe, VI, X-Ray. In conclusion, DD ensures a viable method for detecting protection of FS and fluoride application methods against caries.Keywords: DIAGNO dent, Fissure sealant, Fluoride, laser.